The Influence of Democratic Parenting Patterns to The Creativity of Early Ages - Desta Alicha Istisaroh (Early Childhood Research Journal (ECRJ), 2020)
Children's creativity is the development of children's behavior to express themselves freely, children can imagine and explore what they do. To increase children's creativity is supported by parenting applied by parents. In addition to parents and family, external factors that affect children's creativity are the school environment and the surrounding community and the parenting patterns applied by parents. Parenting patterns include love and affection, and a good relationship between parents and children, the attitude parents show to children, and various rules created by parents to control children's behavior.